Pengaruh Persepsi Mayarakat Kepada Pelayanan Kepolisian di Polsek Tambun Selatan - Ningrum, Firza Ramadhaniar; Merdiaty, Netty (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to determine whether there is an influence between the quality of police services and public perception by using service quality and perception variables. The method used in this research is linear regression analysis with a quantitative approach. The sample in this study consisted of 130 respondents who were selected using purposive sampling technique. The results in this study show an R square value of 0.140 or can be interpreted as 14%. This value provides an explanation that service quality as an independent variable influences perceptions as a dependent variable by 14% while 13.3% is influenced by theoretical factors that are not explained in the research. The results of this research show that there is a negative and significant influence between the quality of police services on community perceptions at the Tambun Selatan Police Station.